Determining factors of perceived elf-efficacy in information seeking practices through Facebook - Giade, Musa Ya’u; Yanti Idaya Aspura, M.K.; Noorhidawati, A. (Malaysian Journal of Library and Information Science, 2018)
The paper reports on factors that drive students’ perceived self-efficacy in information seeking practices through Facebook. The quantitative study employed random sampling of postgraduate students in a higher learning institution. A total of 354 responses were gathered through a self-reported survey. The findings showed four factors, namely, past performance, other’s experience, verbal persuasion and psychological state, have statistically significant correlations with students’ perceived self-efficacy in information seeking practices through Facebook. Past performance was found to be the most influential factor followed by other’s experience. Verbal persuasion and psychological states were the least influential factor. The outcome of the study contributes to the existing literature particularly on the self-efficacy standpoint in social networking sites (SNS) platform. In addition, the findings are relevant to the field of information seeking behaviour especially in providing evidence that people are searching information using Facebook